KEPASTIAN HUKUM PENGAKUAN PUTUSAN GANTI KERUGIAN LINGKUNGAN HIDUP SEBAGAI UTANG DALAM DAFTAR PIUTANG TETAP - Reza Kurnia Akbar; Dedi Harianto; Sunarmi Sunarmi (Smart Education, 2026)
Abstract: The implementation of the environmental damage compensation decision that has permanent legal force is not synchronized with the bankruptcy mechanism, where the state's claim for ecological restoration must compete with other creditors and is subject to strict procedures for matching receivables. The curator's rejection of the KLHK bill in the PT RKK case shows that the obligation for environmental compensation that is public and strategic is actually hampered by the formal time limit in the Bankruptcy Law and PKPU, thus raising questions about the effectiveness of environmental decisions as the basis for debt and the legal protection of the state as an environmental creditor in the bankruptcy process. With the research method used in this study, namely normative juridical, normative juridical research is